Namibia : 2012 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2013)
This report reviews economic development of Namibia in the recent years after the global crisis. The country bounced back very well after the crisis. Namibia exhibited strong performance in the primary sectors, which has led to remarkable growth in the second half of 2012. The government has launched a three-year fiscal initiative to enhance job opportunities and preserve fiscal and external sustainability. Plans have been identified to strengthen banks, control mortgages, and improve the education system. The Executive Board has appreciated Namibia's strong macroeconomic performance.